Distribution, Range and Habitat of the bottlenose dolphin in the ADRION Region - Azzolin, Marta; Arcangeli, Antonella; Costantino, Matteo; Crosti, Roberto; Favaro, Livio; Gamba, Marco; Giacoma, Cristina (Biologia Marina Mediterranea, 2025)
Since December 2014, a systematic survey of cetaceans has been conducted in the Adriatic and Ionian Seas using ferries as observation platforms. This research, coordinated by the University of Torino, Gaia Research Institute and ISPRA's FLT-Med Network, aims to monitor cetacean activity in both inshore and offshore areas of the ADRION Region. Over nine years, the study shows the bottlenose dolphin (Tursiops truncatus) as one of the most frequently sighted species. The research highlights that the distribution and range of bottlenose dolphins, obtained with SPUE and Kernel Density Estimation analysis, vary across seasons, with higher sightings in spring and summer. Employing the Species Distribution Model, the study maps their habitat, showing more extensive suitable areas during warmer months. Understanding the seasonal ecology and habitat suitability of bottlenose dolphins will assist in developing targeted conservation measures to protect this highly mobile species.